Penerapan Smart Indoor Farming dan Clean Energy Technology untuk Peningkatan Kualitas Produksi Hidroponik - Stephanie, Stephanie; Jovin Kendrico; Vanesia Roselin; Winar Joko Alexander; Ziven Louis; Okky Putra Barus (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Global Food Security Index publication notes that Indonesia's food security condition is below the global average. One of the main factors contributing to this issue is climate change and extreme weather. To address this problem, communities can create self-sufficient food sources through home hydroponic farming. Syifa Hidroponik Satu, an MSME in North Sumatra, has been a pioneer in hydroponic plant education and cultivation. However, Syifa Hidroponik Satu faces several production issues, including uncontrolled pests, unpredictable sunlight intensity, high electricity consumption, and inefficient farm monitoring. To overcome these problems, the "Future Farmers" team from Universitas Pelita Harapan implemented smart indoor farming technology and clean energy technology. This technology allows the regulation of temperature, nutrients, pH, and light through an IoT system, and the use of solar panels for energy efficiency. This implementation has successfully improved the quality and productivity of hydroponic farming at Syifa Hidroponik Satu. With these follow-up actions, it is hoped that the quality and productivity of hydroponic farming will continue to increase, making a significant contribution to local food security and supporting greener and more sustainable agriculture.